Single nucleotide polymorphisms of autophagy‐related 16‐like 1 gene are associated with ankylosing spondylitis in females: a case–control study. (26th September 2017) - Li, Xiaona; Chen, Mengya; Zhang, Xu; Wang, Mengmeng; Yang, Xiao; Xia, Qing; Han, Renfang; Liu, Rui; Xu, Shengqian; Xu, Jianhua; Shuai, Zongwen; Pan, Faming
Abstract: Aims: To investigate the associations of autophagy‐related 16‐like 1 ( ATG16L1 ) gene single nucleotide polymorphisms (SNPs) with ankylosing spondylitis (AS) in a Chinese Han population. Methods: Six hundred and forty‐nine AS patients from the First Affiliation Hospital of Anhui Medical University and 628 matched controls were selected. Genotyping for five SNPs in the ATG16L1 gene (rs4663421, rs2241880, rs4663396, rs6758317 and rs6431655) was performed using the improved multiplex ligase detection reaction (iMLDR) method. Haplotypes were built after linkage disequilibrium (LD) analysis. All analyses were stratified by gender. Results: Significant differences in the genotype frequencies at rs4663421 were found between female AS patients and female controls ( P = 0.033). The frequencies of allele G of rs4663421 and allele C of rs6758317 were lower in AS patients than controls (odds ratio [OR] = 0.391, 95% CI = 0.175–0.876, P = 0.019; OR = 0.499, 95% CI = 0.263–0.949, P = 0.032, respectively) in females. However, no association remained significant after Bonferroni correction. rs4663396 and rs6758317 have been tested in high LD, and were used to construct three haplotypes: ht1 (CC), ht2 (TT) and ht3 (CT). The frequency of ht2 (TT) haplotype was higher in AS patients than controls (OR = 2.003, 95% CI = 1.053–3.808, P = 0.032) in females; similarly, no association existed after Bonferroni correction. Conclusions: Two SNPs (rs4663421 and rs6758317) and the TT haplotype of the ATG16L1 gene are possibly associated with AS susceptibility in a Chinese Han female population.